An Inorganic‐Dominate Molecular Diluent Enables Safe Localized High Concentration Electrolyte for High‐Voltage Lithium‐Metal Batteries. (28th November 2022) - Liu, Qianqian; Liu, Yan; Chen, Zerui; Ma, Qiang; Hong, Youran; Wang, Jianghao; Xu, Yifei; Zhao, Wei; Hu, Zhikun; Hong, Xiang; Wang, Jiangwei; Fan, Xiulin; et al.
Abstract: The development of high‐voltage Lithium‐metal batteries (LMBs) is hindered by suitable electrolytes that are simultaneously compatible with both high‐voltage cathodes and Li anodes. Herein, a novel localized high‐concentration electrolyte with ethoxy(pentafluoro)cyclotriphosphazene (PFPN) as a nonflammable diluent is developed. The inorganic‐dominate diluent improves the safety of the organic electrolyte, and helps to construct robust passivation interphases on both electrodes. Specifically, PFPN accelerates the complete reduction of anions, leading to a stable anion‐derived interphase layer on Li anode. Meanwhile, PFPN and anions co‐participate in the formation of cathode‐electrolyte interphase, suppressing side reactions and the structural damage of high‐voltage Ni‐rich cathodes. As a result, PFPN‐based electrolyte prolongs the cycling life of LMBs based on high‐voltage LiNi0.6 Co0.2 Mn0.2 (NCM622) and LiNi0.8 Co0.1 Mn0.1 (NCM811) cathodes. Specially, 25‐µm‐thick Li paired with NCM622 with a N/P ratio of 1.3 (4.4 V) exhibits excellent capacity retention of above 90% after 200 cycles. This study highlights the important role of diluent in tailoring electrode/electrolyte interphases and provides a new strategy for designing high‐safety electrolytes toward high‐voltage LMBs. Abstract : In this work, a novel inorganic‐dominate molecular diluent for localized high concentration electrolyte (LHCE) is proposed, exemplified by ethoxy (pentafluoro) cyclotriphosphazene (PFPN). PPFN diluted LHCE not only improves the lifespan of high voltage LMBs over a wide temperature range by stabilizing both electrodes but also improves cell safety benefiting from the flame retardancy of PFPN.